The potency of plankton as natural food for hard-lipped barb larvae (Osteochilus hasselti C.V.) - Niken Tunjung Murti Pratiwi; . Winarlin; Yuki Hana Eka Frandy; Aliati Iswantari (Jurnal Akuakultur Indonesia)
Plankton is aquatic organism that can be utilized as natural food. Hard-lipped barb is one of herbivorous fish that most of its life using plankton as its food source. Growing phytoplankton in pond can be conducted by providing nutrient source, such as fertilizing.  In this study, we examined the growth of hard-lipped barb larvae related to the existence of natural food in different fertilized ponds.  Four types of fertilizer were applied i.e. 100% organic fertilizer (PO), mixing of 85% organic and 15% inorganic fertilizer (PCa), mixing of 60% organic and 40% inorganic fertilizer, and 100% inorganic fertilizer (PA). Hard-lipped barb larvae were put into ponds after fertilizing process. Plankton was observed in ponds and larval intestines (Index of Preponderance and Ivlev Index). The growth of hard-lipped barb larvae was also observed. The result showed that larvae tend to utilize phytoplankton from the class of Bacillariophyceae and zooplankton in the early of its life. Utilizing plankton with those compositions as natural food in the early period generates a good growth performance.  The best performance of growth was shown by larvae in PA treatment which utilized most on zooplankton in the early period.